Studies in de performance of late mediaeval music - Boorman, Stanley (Cambridge Cambridge University Press, 1983)
This volume presents a series of important essays by American and European scholars on some of the problems involved in attempting to perform music of the late Middle ages. The essays are based on papers read at a conference held at the New York University Center for Early Music in 1981 and they concern a varied selection of aspects of the subject; behind many lies an interest in the reopened question of how far instruments had a role in performing secular or sacred music. Among the questions tackled are: the types of harps found in fourteenth-century Italy, and their probable uses; the numbers of singers needed (with their ranges) for fourteenth-century English music; evidence for the use of instruments in the thirteenth century and for wind articulation in the late fourteenth; specific performing ensembles of the fifteenth century, and what they may have sung in a polyphonic Mass.